THE ROLE OF FAMILY DYNAMICS IN MANAGING CLINICAL DEPRESSION: INSIGHTS FROM THERAPY - Dara Van; Ravi Dara; Sota Yamamoto (Research Psychologie, Orientation et Conseil, 2026)
Clinical depression is a complex mental health condition that often involves not only individual psychological factors but also familial and social dynamics. Understanding the role of family interactions in managing clinical depression is crucial for developing more effective therapeutic interventions. This study aims to explore how family dynamics influence the management of clinical depression from a therapeutic perspective, focusing on communication patterns, emotional support, and conflict resolution within family units. A qualitative research design was employed, using semi-structured interviews with 20 individuals undergoing therapy for clinical depression. Family members of the participants were also interviewed to understand their roles in the therapeutic process. Data was analyzed using thematic analysis to identify key patterns related to family involvement in managing depression. The findings reveal that family dynamics significantly affect the course of treatment. Positive communication, emotional support, and active involvement in therapy contributed to better treatment outcomes. Conversely, family conflict and poor communication were associated with less favorable therapeutic progress. Family dynamics play a crucial role in managing clinical depression. This research emphasizes the importance of incorporating family therapy in the treatment process to enhance the effectiveness of clinical interventions and improve patient well-being.